Comparison of Squamous Cell Carcinoma of the Tongue between Young and Old Patients - Gyuheon Choi; Joon Seon Song; Seung-Ho Choi; Soon Yuhl Nam; Sang Yoon Kim; Jong-Lyel Roh; Bu-Kyu Lee; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background The worldwide incidence of squamous cell carcinoma of the tongue (SCCOT) in young patients has been increasing. We investigated clinicopathologic features of this unique population and compared them with those of SCCOT in the elderly to delineate its pathogenesis. Methods We compared clinicopathological parameters between patients under and over 45 years old. Immunohistochemical assays of estrogen receptor, progesterone receptor, androgen receptor, p53, p16, mdm2, cyclin D1, and glutathione S-transferase P1 were also compared between them. Results Among 189 cases, 51 patients (27.0%) were under 45 years of age. A higher proportion of women was seen in the young group, but was not statistically significant. Smoking and drinking behaviors between age groups were similar. Histopathological and immunohistochemical analysis showed no significant difference by age and sex other than higher histologic grades observed in young patients. Conclusions SCCOT in young adults has similar clinicopathological features to that in the elderly, suggesting that both progress via similar pathogenetic pathways.